Extracellular vesicles from endometriosis patients are characterized by a unique miRNA-lncRNA signature - Khalaj, Kasra (JCI Insight, 2019)
With multifactorial etiologies, combined with disease heterogeneity and a lack of suitable diagnostic markers and therapy, endometriosis remains a major reproductive health challenge. Extracellular vesicles (EVs) have emerged as major contributors of disease progression in several conditions, including a variety of cancers; however, their role in endometriosis pathophysiology has remained elusive. Using next-generation sequencing of EVs obtained from endometriosis patient tissues and plasma samples compared with controls, we have documented that patient EVs carry unique signatures of miRNAs and long noncoding RNAs (lncRNAs) reflecting their contribution to disease pathophysiology. Mass spectrophotometry–based proteomic analysis of EVs from patient plasma and peritoneal fluid further revealed enrichment of specific pathways, as well as altered immune and metabolic processes. Functional studies in endometriotic epithelial and endothelial cell lines using EVs from patient plasma and controls clearly indicate autocrine uptake and paracrine cell proliferative roles, suggestive of their involvement in endometriosis. Multiplex cytokine analysis of cell supernatants in response to patient and control plasma–derived EVs indicate robust signatures of important inflammatory and angiogenic cytokines known to be involved in disease progression. Collectively, these findings suggest that endometriosis-associated EVs carry unique cargo and contribute to disease pathophysiology by influencing inflammation, angiogenesis, and proliferation within the endometriotic lesion microenvironment.